Plasma beta effects on the edge magnetic field structure and divertor heat loads in Wendelstein 7-X high-performance scenarios. (20th December 2021) - Knieps, A.; Suzuki, Y.; Geiger, J.; Dinklage, A.; Zhou, S.; Rahbarnia, K.; Schilling, J.; Neuner, U.; Thomsen, H.; Jakubowski, M.; Koenig, R.; Endler, M.; et al.
Abstract: To support the scenario design for the upcoming long-pulse high-performance campaign of Wendelstein 7-X, this work presents a study of high-beta full-field 3D equilibria obtained with the HINT code. For three magnetic configurations of different edge- ι, the effects of both overall pressure and pressure profile changes on the magnetic topology are analyzed. Anisotropic diffusion modeling is used to obtain estimates of the conductive heat load distribution both on the divertor and other plasma-facing components in finite-beta magnetic configurations. For the magnetic standard configuration, limitations of the model are outlined by comparing measured and predicted heatloads by performing a linear regression of the main strike-line position against various plasma parameters in both the experimental and the simulated device.